KENDALI PROPORSIONAL INTEGRAL PADA KECEPATAN MOTOR ARUS SEARAH TANPA SIKAT - mowaviq, Muhammad Imbarothur; Delila Cahya Permatasari; Irfin Sandra Asti; Erlillah Rizqi Kusuma Pradani (Jurnal Informatika dan Teknik Elektro Terapan, 2026)
Brushless Direct Current (BLDC) motors have become a fundamental drive technology in various modern industries, from automotive to aerospace, thanks to their superior efficiency and long operational life. The precision operation of BLDC motors is highly dependent on accurate rotor position information, which is provided by hall sensors. These sensors send signals to a control unit that performs electronic commutation to drive the motor. However, to achieve optimal system response, the implementation of an additional control system is required. This research focuses on the design, implementation, and performance analysis of Proportional Integral (PI) control to regulate the speed of BLDC motors. Based on this target, a proportional control of 0.01990 and an integral gain of 3.29063 are obtained. The simulation results show the system response to a step input with a setpoint of 500 rpm. The motor speed successfully reached 450 rpm in 0.3 seconds, but only stabilized at the setpoint of 500 rpm after reaching 2.5 seconds. The response results also showed ripples in the motor speed, although not significant, caused by non-linear factors inherent in the BLDC motor control system.